DEHP degradation and dechlorination of polyvinyl chloride waste in subcritical water with alkali and ethanol: A comparative study. (June 2020) - Xiu, Fu-Rong; Lu, Yongwei; Qi, Yingying
Abstract: In this study, subcritical water-NaOH (CW–NaOH) and subcritical water-C2 H5 OH (CW–C2 H5 OH) processes were developed for diethylhexyl phthalate (DEHP) degradation and dechlorination of polyvinyl chloride (PVC) waste. The introduction of NaOH or C2 H5 OH in subcritical water had a noticeable influence on the mechanism of DEHP degradation and dechlorination. For both CW-NaOH and CW-C2 H5 OH treatments, the increase in temperature could increase dechlorination efficiency (DE) of PVC. The DE of CW-NaOH is much higher than that of CW-C2 H5 OH under the same conditions. The DE of CW-NaOH could exceed 95% at 300 °C. Hydroxyl nucleophilic substitution was the main dechlorination mechanism in CW-NaOH, while nucleophilic substitution and direct dehydrochlorination were equally important in CW-C2 H5 OH. In CW-NaOH treatment, 2-ethyl-1-hexanol, benzaldehyde, and toluene were obtained by hydrolysis and reduction reactions of DEHP. Acetophenone was produced by the further cyclization, dehydrogenation and rearrangement reactions of 2-ethyl-1-hexanol. Transesterification was the main degradation pathway of DEHP in CW-C2 H5 OH at 300 °C. The cyclization and dehydration of 2-ethyl-1-hexanol resulted in producing a high level of ethyl-cyclohexane and 1-ethyl-cyclohexene in CW-C2 H5 OH at 350 °C. Furthermore, high concentration of ethyl palmitate and ethyl stearate could be prepared in CW-C2 H5 OH system by the strong reactivity of C2 H5 OH with the lubricants in PVC. Graphical abstract: Image 1 Highlights: We report two effective processes for DEHP degradation and dechlorination of PVC. CW-NaOH and CW-C2 H5 OH have different DEHP degradation and dechlorination mechanism. Hydrolysis and reduction were the main degradation pathways of DEHP in CW-NaOH. Transesterification was the main degradation pathway of DEHP in CW-C2 H5 OH. Nucleophilic substitution and dehydrochlorination co-existed in dechlorination.